Table of Contents (European Journal of Transport and Infrastructure Research, 2017)
Editorial board The other side of an airport’s two-sided market: issues in planning and pricing airport surface access Pages 442-456 K.Button Testing the stability of utility parameters in repeated best, repeated best-worst and one-off best-worst studies Pages 457-476 M. Giergiczny, T. Dekker, S. Hess and P.K.C. Chintakayala The effect of wind turbines alongside motorways on drivers’ behaviour Pages 477-494 T. De Ceunynck, E. De Pauw, S. Daniels, E. Polders, T. Brijs, E. Hermans and G. Wets Public Infrastructure and Regional growth: Evidence from Turkey Pages 495-507 Z. Elburz, P. Nijkamp and E. Pels Modelling sailing time and cost for inland waterway transport Pages 508-529 R.G. Hekkenberg, C. Van Dorsser and J. Schweighofer Measuring highway efficiency by a DEA approach and the Malmquist index Pages 530-551 J. Sarmento, L. Renneboog and P.V. Matos